2010
DOI: 10.1039/b924736j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and catalytic performances of hierarchical SAPO-34 monolith

Abstract: A novel hierarchical SAPO-34 monolith was prepared by the dry gel conversion of the amorphous silicoaluminophosphate monolith. The obtained material possesses macropores and mesopores besides micropores. The macroporous framework of the hierarchical SAPO-34 is constructed by interconnected spherical aggregates of cubic SAPO-34 crystals and mesopores is formed by the close stacking of cubic SAPO-34 crystals. Catalytic tests show that the hierarchical SAPO-34 possesses high catalytic activity compared with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
84
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 27 publications
2
84
1
2
Order By: Relevance
“…However, the latter catalyst has a much shorter lifetime than ZSM-5 due to the extension of coking reactions inside the cages of the CHA structure, and a continuous catalyst regeneration process is required. Lifetime of SAPO-34 can be extended by using mesoporous SAPO-34 [8][9][10][11][12], by decreasing the size of the crystal [13][14][15][16][17][18] or by including metal oxides in the catalyst composition [19]. Smaller crystallites of SAPO-34 were achieved recently by heating the synthesis gel in a microwave apparatus [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter catalyst has a much shorter lifetime than ZSM-5 due to the extension of coking reactions inside the cages of the CHA structure, and a continuous catalyst regeneration process is required. Lifetime of SAPO-34 can be extended by using mesoporous SAPO-34 [8][9][10][11][12], by decreasing the size of the crystal [13][14][15][16][17][18] or by including metal oxides in the catalyst composition [19]. Smaller crystallites of SAPO-34 were achieved recently by heating the synthesis gel in a microwave apparatus [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its application prospect and future development in modern petrochemical industry are restrained greatly [16], especially for the conversion of large molecules as those encountered in heavy crude oil catalytic cracking process [17,18]. In order to overcome limitations of single microporous or mesoporous molecular sieves and to make preponderance complementarity between the two type molecular sieves, some research groups had extended new synthesis strategy to prepare mesoporous SAPO [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that macroporous SAPO-34 can be prepared by using a dry gel conversion method. However, the macropores are actually an aggregated structure and could easily be changed by changing the conditions used for synthesis [19]. Polystyrene spheres (PS) as hard templates have attracted much attention [20,21].…”
Section: Introductionmentioning
confidence: 99%